Social Work and Follow up to Graduates at the Universidad Tecnica de ManabÃ - Barreiro, Leila ÃƒÂlava; MenÃƒÂ©ndez, FabiÃƒÂ¡n Gustavo MenÃƒÂ©ndez; Medranda, Eva AlcÃƒÂvar; Sornoza, Karol Liceth Pico (International Research Journal of Management, IT & Social Sciences, 2017)
A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and conclusions...